Włoska teologia fundamentalna - Skierkowski, Marek (Śląskie Studia Historyczno-Teologiczne, 2011)
The article concerns the Italian Fundamental Theology, which derived from the classical Apologetics. The Italian theologians worked out their own model of Fundamental Theology as a theology of the Revelation and its credibility (R. Fisichella, C. Dotolo, C. Greco, A. Toniolo, G. Lorizio, G. Tanzella-Nitti, M. Epis). Apart from this model another concept is also being developed, namely a theological treatise de fide (P. Sequeri, F. Cappa).